2011
DOI: 10.1159/000322937
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Behaviour and Self-Esteem following Growth Hormone Treatment in Short Prepubertal Children

Abstract: Background/Aims: To evaluate effects of growth hormone (GH) treatment on behaviour and psychosocial characteristics in short-stature children. Methods: 99 referred prepubertal non-familiar short-stature children (32 GH deficiency; 67 idiopathic short stature) aged 3–11 years, randomized to fixed or individual GH doses and their parents completed questionnaires (Child Behaviour Checklist, Birleson Depression Self-Report Scale, Abbreviated Parent-Teacher Questionnaire, I Think I Am, Well-Being Visual-Analogue Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 73 publications
(51 reference statements)
6
51
0
2
Order By: Relevance
“…This is in line with previous studies, showing on average lower intelligence and more behaviour, social functioning, school competence and attention problems in short SGA children [24,25,26,27,28]. During GH treatment, improvement of intelligence, behaviour and self-perception has been described in short SGA children [28], as well as improvement of behaviour and self-esteem in short children with GH deficiency and idiopathic short stature [29,30]. According to a recent systematic review, however, data on HRQoL before and during GH treatment in short children are lacking [11].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous studies, showing on average lower intelligence and more behaviour, social functioning, school competence and attention problems in short SGA children [24,25,26,27,28]. During GH treatment, improvement of intelligence, behaviour and self-perception has been described in short SGA children [28], as well as improvement of behaviour and self-esteem in short children with GH deficiency and idiopathic short stature [29,30]. According to a recent systematic review, however, data on HRQoL before and during GH treatment in short children are lacking [11].…”
Section: Discussionsupporting
confidence: 91%
“…An increase of self-esteem has also been reported in a previous study of GH treatment of GHD children [27]. This increase may be caused by the increased growth velocity under treatment, the happiness to have reached the 10th percentile starting from below the 3rd percentile, or the effect of receiving services and being understood and supported.…”
Section: Discussionsupporting
confidence: 65%
“…Our recent research has emphasized the importance of trying to individualize the GH dosing according to responsiveness [11] in order to achieve optimal and safe attainment of the target height [12,13]. The study design and results of the clinical trial have been reported elsewhere [13,14,15]. Subjects and their parents in four of the centers completed psychosocial evaluations at study start, and after 3, 12 and 24 months of GH treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The study population included girls 3–10 years of age and boys 3–11 years at study start with height SDS no greater than –2 SDS compared to the population norms and 1 SDS or more below MPH (MPH SDS ). Further details of the study sample can be found in our previous publications [13,15]. …”
Section: Methodsmentioning
confidence: 99%